Efficacy of stabilisation splint treatment on the oral health-related quality of life-A randomised controlled one-yearfollow-up trial - Kokkola O; Suominen AL; Qvintus V; Myllykangas R; Lahti S; Tolvanen M; Sipilä K (WILEY, 2022)
The aim of this randomised controlled trial was to assess the efficacy of stabilisation splint treatment on the oral health-related quality of life OHRQoL during a 1-year follow-up. Originally, the sample consisted of 80 patients (18 men, 62 women) with temporomandibular disorders (TMD) who had been referred to the Oral and Maxillofacial Department, Oulu University Hospital, Finland, for treatment. Patients were randomly designated into splint (n=39) and control group (n=41). Patients in the splint group were treated with a stabilisation splint. Additionally, patients in both groups received counselling and instructions on masticatory muscle exercises. The patients filled in the Oral Health Impact Profile-14 (OHIP-14) questionnaire before treatment and at 3months, 6months and 1year. At total, 67 patients (35 in the splint group vs. 32 in the control group) completed the questionnaire at baseline. The outcome variables were OHIP prevalence, OHIP severity and OHIP extent. Linear mixed-effect regression model was used to analyse factors associated with change in OHIP severity during the 1-year follow-up, taking into account treatment time, age, gender and group status. OHIP prevalence, severity and extent decreased in both groups during the follow-up. According to linear mixed-effect regression, decrease in OHIP severity did not associate significantly with group status. Compared to masticatory muscle exercises and counselling alone, stabilisation splint treatment was not more beneficial on self-perceived OHRQoL among TMD patients over a 1-year follow-up